2021
DOI: 10.3724/sp.j.1089.2021.18392
|View full text |Cite
|
Sign up to set email alerts
|

Siamese Progressive Attention-Guided Fusion Network for Object Tracking

Abstract: For the most of object tracking algorithms using siamese networks, the semantic feature derived from the last layer of the backbone network is used to calculate the similarity. However, the use of single deep feature space often leads to partial loss of effective information. To address this issue, the siamese progressive attention-guided fusion network is proposed. First, the deep and shallow feature information is simultaneously extracted using the backbone network. Second, a top-down strategy is adopted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The literature [17] extracts deep features and uses the integrated idea to obtain a stronger tracking model. The literature [18] introduces continuous convolution operators to solve the learning problem of continuous space; On the other hand, directly using deep learning algorithms for target tracking, such as multi-domain convolutional neural network structure system network is applied to target tracking [19], and literature [20] proposed an online visual tracking algorithm based on a tree structure to manage multiple target appearance models, with better results. Studies have shown that the direct use of deep learning algorithms for end-to-end target tracking is more suitable for development needs.…”
Section: Related Workmentioning
confidence: 99%
“…The literature [17] extracts deep features and uses the integrated idea to obtain a stronger tracking model. The literature [18] introduces continuous convolution operators to solve the learning problem of continuous space; On the other hand, directly using deep learning algorithms for target tracking, such as multi-domain convolutional neural network structure system network is applied to target tracking [19], and literature [20] proposed an online visual tracking algorithm based on a tree structure to manage multiple target appearance models, with better results. Studies have shown that the direct use of deep learning algorithms for end-to-end target tracking is more suitable for development needs.…”
Section: Related Workmentioning
confidence: 99%